2010
DOI: 10.1111/j.1365-2605.2009.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A concentrations and ovarian response among women undergoing IVF

Abstract: Summary Bisphenol A (BPA) is a synthetic chemical used in the manufacture of materials present in many common consumer products. In experimental animals, BPA caused oocyte aneuploidy and reduced production of oestradiol. In a prospective cohort study, we investigated the association between urinary BPA concentrations and ovarian response among women undergoing in vitro fertilization (IVF) at the Massachusetts General Hospital (MGH) Fertility Center. The geometric mean of two specific-gravity (SG) adjusted urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(166 citation statements)
references
References 46 publications
4
158
1
3
Order By: Relevance
“…5D). [218][219][220][221][222]267 Thus, collectively, these studies suggest that low dose BPA exposure exerts adverse effects on growing follicles in the adult ovary.…”
Section: Integration Of Endpoints Across Levels Of Biological Organizmentioning
confidence: 76%
See 1 more Smart Citation
“…5D). [218][219][220][221][222]267 Thus, collectively, these studies suggest that low dose BPA exposure exerts adverse effects on growing follicles in the adult ovary.…”
Section: Integration Of Endpoints Across Levels Of Biological Organizmentioning
confidence: 76%
“…Several prospective IVF cohort studies examined associations between BPA and early IVF outcomes in women. [218][219][220][221][222] Significant negative associations between BPA and peak ovarian estradiol were observed in multiple cohorts, although other associations were only observed in a single cohort (i.e., oocyte yield, and other downstream IVF outcomes). In one cohort, later reproductive endpoints (i.e., embryo implantation) were negatively associated with urinary BPA concentrations.…”
Section: -53mentioning
confidence: 99%
“…Human chorionic gonadotropin (hCG) was administered approximately 36 hr before the scheduled egg-retrieval procedure to induce ovulation. Details of egg retrieval have been previously described (18). …”
Section: Methodsmentioning
confidence: 99%
“…It has also been found in detectable amounts in dust [193 -196]. Urine BPA levels of women undergoing infertility treatment is negatively correlated with the number and quality of eggs retrieved, and with serum E 2 levels [197,198]. BPA has been shown to have estrogenic properties and that it can be transferred both lactationally and transplacentally [190,199].…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%
“…Another effect of BPA is exerted at the level of oogenesis and is of very high concern [197]. Studies from Hunt and colleagues demonstrated that BPA released from damaged animal cages and water bottles, which were inadvertently treated with harsh alkaline detergent, induced defects in the meiotic prophase stage of oocyte development in mice: oocytes had increased levels of meiotic aneuploidy due to congression failure.…”
Section: Bpa In Vivo Studiesmentioning
confidence: 99%